High-permeability and high-viscosity asphalt pavement crack pouring material based on gold tailings as well as preparation method and use method of high-permeability and high-viscosity asphalt pavement crack pouring material

By using high -lying high -viscosity asphalt pavement materials made of gold tailings powder and other materials, the problems of the existing materials on the environment and human health under high temperature conditions and cost and construction efficiency are solved. Sonability, high adhesion and long life.

CN119371142APending Publication Date: 2025-01-28SHANDONG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411559944.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing asphalt pavement seam filling materials release volatile organic matter under high temperature conditions, which poses harm to the environment and human health. It has high production and use costs, low construction efficiency and insufficient durability.

Method used

Using high -lying height and high -lying asphalt pavement materials based on gold tail mines, it is made of golden tail mine powder, rock asphalt, mineral powder, lime, petroleum resin, aromatic oil and rubber powder according to a specific proportion, and heated and stirred. The material has high permeability, high adhesion and long service life.

Benefits of technology

A large amount of golden tail mines have been achieved. The materials have high permeability, high adhesion, and long service life. The construction is simple and the solidified time can be opened by 15 to 20 minutes after the launch of the road. Time closed the road.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371142A_ABST
    Figure CN119371142A_ABST
Patent Text Reader

Abstract

The invention discloses a high-permeability and high-viscosity asphalt pavement crack pouring material based on gold tailings as well as a preparation method and a use method of the high-permeability and high-viscosity asphalt pavement crack pouring material, and belongs to the technical field of crack pouring materials. The asphalt pavement crack pouring material comprises the following raw materials in parts by weight: 8-15 parts of rock asphalt, 30-50 parts of gold tailing powder, 5-15 parts of mineral powder, 5-15 parts of lime, 2-6 parts of petroleum resin, 20-30 parts of aromatic hydrocarbon oil and 5-10 parts of rubber powder. The asphalt pavement crack pouring material can realize the consumption of a large amount of gold tailings, and has the advantages of high permeability, high cohesiveness, long service life, low raw material cost and no need of complex treatment steps; and moreover, construction is easy and convenient, curing time is short, traffic can be opened 15-20 minutes after the paint is applied to pavement cracks, and long-time road closing is not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of caulking materials, and in particular to a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, and a preparation method and a use method thereof. Background Art

[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Asphalt pavement caulking materials play a vital role in road maintenance. With the increase in road traffic, the problem of pavement cracks has become increasingly serious, and effective repair materials are needed to extend the service life of the pavement. Existing asphalt pavement caulking materials mainly include modified asphalt caulking materials, shallow grouting materials and fiber-reinforced caulking materials. Modified asphalt caulking materials are often used to repair cracks on the road surface. These materials improve the adhesion and elasticity of the material by adding modifiers (such as SBS, SBR, etc.) to asphalt. However, modified asphalt materials will release volatile organic compounds under high temperature conditions, which is harmful to the environment and human health. In addition, the production and use costs of modified asphalt materials are high, which increases the economic burden of road maintenance.

[0004] Shallow grouting materials and fiber-reinforced grouting materials improve the repair effect by filling cracks and strengthening the pavement structure. These materials require complex construction processes and equipment during use, have low construction efficiency, and are not durable enough under some extreme climatic conditions.

[0005] Gold tailings are solid waste generated after gold ore is flotated and extracted. The accumulated stockpile has reached more than 1.5 billion tons, but the utilization rate is less than 30%. The traditional treatment method is to store it in a tailings pond or fill it in a pit. The area of ​​the tailings pond increases by 300 to 400 km per year on average. 2 At present, the research field mainly uses gold tailings to prepare cement and concrete, and enhances the gelling activity by adding alkaline activators, but there are few studies on asphalt.

[0006] At present, there is no report on asphalt pavement caulking materials with gold tailings as the main component. Asphalt pavement caulking materials must have good adhesion, permeability, fluidity and economic durability. Therefore, how to provide a low-cost, high-permeability and high-viscosity asphalt pavement caulking material with solid waste gold tailings as the main component is an urgent problem to be solved. Summary of the invention

[0007] In view of this, the present invention provides a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, and a preparation method and a use method thereof. The asphalt pavement caulking material provided by the present invention has high permeability, high adhesion and a long service life, and at the same time a short curing time. It can be opened to traffic 15 to 20 minutes after being applied to pavement cracks. It is easy to operate and has low cost.

[0008] In a first aspect, the present invention provides a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, comprising the following raw materials in parts by weight: 8 to 15 parts of rock asphalt, 30 to 50 parts of gold tailings powder, 5 to 15 parts of mineral powder, 5 to 15 parts of lime, 2 to 6 parts of petroleum resin, 20 to 30 parts of aromatic oil and 5 to 10 parts of rubber powder.

[0009] Preferably, the fineness of the gold tailings powder is 50-1500 mesh.

[0010] Preferably, the petroleum resin is selected from at least one of aliphatic petroleum resin, aromatic hydrocarbon petroleum resin or cycloaliphatic diene petroleum resin.

[0011] Preferably, the aromatic oil is selected from one or more of furfural extracted oil, phenol extracted oil and methyl pyrrolidone extracted oil.

[0012] Preferably, the fineness of the rubber powder is 40-100 meshes.

[0013] In a second aspect, the present invention provides a method for preparing the high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings, comprising the following steps:

[0014] Preheating and mixing the petroleum resin and the aromatic oil to form a liquid mixture;

[0015] The rock asphalt, gold tailings powder, mineral powder, lime and rubber powder are heated and dry-mixed to obtain a powdery mixture;

[0016] The liquid mixture is added into the powder mixture, heated and stirred to obtain the product.

[0017] Preferably, the preheating mixing temperature is 150-200°C.

[0018] Preferably, the temperature of the heating and dry mixing is 180-200°C.

[0019] Preferably, the heating and stirring temperature is 260-280° C., the stirring speed is 600-1000 rpm, and the heating and stirring time is more than 30 min.

[0020] In a third aspect, the present invention provides a method for using the high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings or the high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings prepared by the above preparation method, comprising the following steps:

[0021] The high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings is poured into the cracks of the pavement while hot, compacted and smoothed, and cooled and solidified for more than 15 minutes.

[0022] Compared with the prior art, the present invention has achieved the following beneficial effects:

[0023] The high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings provided by the present invention has gold tailings solid waste as the main component, can realize the large-scale disposal of gold tailings, and has high permeability, high adhesion and a long service life. At the same time, the raw material cost is low and no complicated processing steps are required; it is also easy to construct and has a short curing time. Traffic can be opened 15 to 20 minutes after being applied to the cracks in the pavement, without the need to close the road for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a picture of the actual application effect of the high-permeability and high-viscosity asphalt pavement crack filling material prepared in Example 2 of the present invention on the pavement of the Jinan section of G105 National Highway;

[0026] Figure 2 This is a picture of the actual application effect of the high-permeability and high-viscosity asphalt pavement caulking material prepared in Example 2 of the present invention on the pavement of the Jinan section of G105 National Highway. DETAILED DESCRIPTION

[0027] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0028] The invention provides a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, comprising the following raw materials in parts by weight: 8 to 15 parts of rock asphalt, 30 to 50 parts of gold tailings powder, 5 to 15 parts of mineral powder, 5 to 15 parts of lime, 2 to 6 parts of petroleum resin, 20 to 30 parts of aromatic oil and 5 to 10 parts of rubber powder.

[0029] In the high-permeability and high-viscosity asphalt pavement caulking material of the present invention, rock asphalt serves as a basic adhesive, provides viscosity and toughness, and is the core component of the caulking material; gold tailings powder serves as fine aggregate to increase the fine aggregate filling and stability of the material, improve the high-temperature stability and adhesion of the material, and is combined with rock asphalt and mineral powder to form a more stable structure, thereby enhancing the overall performance of the mixture; mineral powder serves as a supplementary filler to improve the fluidity and construction performance of the caulking material, and simultaneously acts with lime to form a certain chemical bond to enhance the cohesion of the mixture, and the two together increase the pH value of the mixture, which helps to improve the binding force with acidic materials, enhance adhesion, and thus improve compatibility with asphalt; petroleum resin increases the viscosity and plasticity of the mixture, improves aging resistance and weather resistance, and is combined with aromatic oil to form a more flexible asphalt mixture; aromatic oil improves the fluidity and construction performance of the mixture, reduces the viscosity of the material, forms good compatibility with petroleum resin, and improves the penetration ductility and flexibility of the mixture; rubber powder can improve the elasticity and crack resistance of the mixture, enhance deformation resistance, and is combined with rock asphalt to improve the wear resistance and fatigue resistance of the mixture.

[0030] In the present invention, the fineness of the gold tailings powder is 50-1500 mesh, more preferably 500-1000 mesh. The gold tailings powder of the present invention is preferably solid waste discarded after gold ore is processed by flotation process and gold extraction process to recover gold or other useful components, rather than tailings after cyanide gold extraction. Gold tailings are selected to be fine and soft, small in particle size, high in temperature resistance, and contain a high content of SiO2, and also contain Al2O3, Fe2O3, CaO and a small amount of metal elements. They have good low temperature performance and ductility in asphalt mortar.

[0031] In the present invention, the petroleum resin is selected from at least one of aliphatic petroleum resin (C5), aromatic hydrocarbon petroleum resin (C9) or cycloaliphatic diene petroleum resin (DCPD).

[0032] In the present invention, the aromatic oil is selected from one or more of furfural extracted oil, phenol extracted oil, and methyl pyrrolidone extracted oil. The boiling point of the aromatic oil selected in the present invention needs to be higher than 320°C.

[0033] In the present invention, the rubber powder has a fineness of 40 to 100 meshes. The rubber powder of the present invention is preferably fine powder obtained by crushing and grinding waste tires, which further reduces the cost and can improve the elasticity and crack resistance.

[0034] The present invention also provides a method for preparing the high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings, comprising the following steps:

[0035] Preheating and mixing the petroleum resin and the aromatic oil to form a liquid mixture;

[0036] The rock asphalt, gold tailings powder, mineral powder, lime and rubber powder are heated and dry-mixed to obtain a powdery mixture;

[0037] The liquid mixture is added into the powder mixture, heated and stirred to obtain the product.

[0038] The present invention does not impose any special restrictions on the equipment used in the above steps, and any mixing and heating equipment commonly used in the art can be used. For example, the mixing equipment can be a twin-screw mixer or a planetary mixer. An online temperature monitoring and automatic control system can be added during the mixing process to ensure that the mixture is operated within the optimal temperature range, thereby improving the consistency and quality of the material.

[0039] In the present invention, the preheating and mixing temperature is 150-200° C., more preferably 160-180° C. At this temperature, the petroleum resin melts and can be better mixed with the aromatic oil.

[0040] In the present invention, the temperature of the heated dry mixing is 180-200°C to ensure that the aggregate is fully preheated. Preheating helps to increase the temperature of the aggregate, so that the petroleum resin and aromatic oil added subsequently can be mixed with the aggregate faster and more evenly. Reduce the possibility of agglomeration of the aggregate due to absorption of aromatic oil. If the aggregate temperature is not enough, the aromatic oil may accumulate in a local area, resulting in uneven mixing. By preheating the aggregate, the time required for heating the entire mixture can be reduced, thereby improving production efficiency.

[0041] In the present invention, the temperature of the heating and stirring is 260-280°C, the speed of stirring is 600-1000 rpm, and the time of heating and stirring is more than 30 minutes, preferably 30-50 minutes. Within this temperature range, the viscosity of the material is reduced, ensuring complete mixing and reaction, so that various components such as asphalt, gold tailings powder, rock asphalt, petroleum resin and aromatic oil are easier to mix evenly.

[0042] The present invention provides a method for using the high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings, comprising the following steps:

[0043] The high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings is poured into the cracks of the pavement while hot, compacted and smoothed, and cooled and solidified for more than 15 minutes.

[0044] The present invention also includes the steps of calibrating the starting position of the crack and removing the debris and loose particles in the crack before the grouting operation, and the crack can be blown away by an air gun. The present invention does not impose any special restrictions on the compaction and smoothing steps after the grouting, and the compaction and smoothing steps commonly used in the art can be used.

[0045] The caulking material is usually applied in the form of a thin strip, with a thickness of 0.5 cm to 2 cm, and the width can be controlled as needed. After the caulking material is applied, as the temperature decreases, the rock asphalt components and petroleum resin in the caulking material will gradually cool and re-harden, restoring their original solid or semi-solid form. The hardened rock asphalt and petroleum resin help provide the cohesion and durability of the caulking material, ensuring the long-term stability of the crack repair.

[0046] The technical solution of the present invention is further described below in conjunction with specific embodiments. In the following embodiments, the fineness of the gold tailings powder is 800-1000 meshes, the petroleum resin is selected from C5 petroleum resin, the aromatic oil is furfural extracted oil, and the rubber powder is a fine powder obtained by crushing and grinding waste tires, with a fineness of 80 meshes.

[0047] Example 1

[0048] The present embodiment provides a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, comprising the following raw materials in parts by weight: 10 parts of rock asphalt, 35 parts of gold tailings powder, 6 parts of mineral powder, 10 parts of lime, 4 parts of petroleum resin, 27 parts of aromatic oil, and 8 parts of rubber powder.

[0049] The preparation method is as follows: weigh the raw materials according to the above ratio, mix the petroleum resin and aromatic oil, preheat to 170°C to form a liquid mixture. Mix the rock asphalt, gold tailings powder, mineral powder, lime and rubber powder evenly, heat and dry mix in an electric heating jacket at 180°C. Pour the liquid mixture preheated to 170°C into the powder mixture at 180°C, continue to heat to 260°C, and stir with a high-speed mixer at 800 rpm for 45 minutes.

[0050] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0051] Example 2

[0052] The present embodiment provides a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, comprising the following raw materials in parts by weight: 12 parts of rock asphalt, 33 parts of gold tailings powder, 6 parts of mineral powder, 9 parts of lime, 5 parts of petroleum resin, 25 parts of aromatic oil, and 8 parts of rubber powder.

[0053] The preparation method is as follows: weigh the raw materials according to the above ratio, mix the petroleum resin and aromatic oil, preheat to 170°C to form a liquid mixture. Mix the rock asphalt, gold tailings powder, mineral powder, lime and rubber powder evenly, heat and dry mix in an electric heating jacket at 180°C. Pour the liquid mixture preheated to 170°C into the powder mixture at 180°C, continue to heat to 260°C, and stir with a high-speed mixer at 800 rpm for 45 minutes.

[0054] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0055] Example 3

[0056] The present embodiment provides a high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, comprising the following raw materials in parts by weight: 8 parts of rock asphalt, 37 parts of gold tailings powder, 5 parts of mineral powder, 11 parts of lime, 3 parts of petroleum resin, 25 parts of aromatic oil, and 10 parts of rubber powder.

[0057] The preparation method is as follows: weigh the raw materials according to the above ratio, mix the petroleum resin and aromatic oil, preheat to 170°C to form a liquid mixture. Mix the rock asphalt, gold tailings powder, mineral powder, lime and rubber powder evenly, heat and dry mix in an electric heating jacket at 180°C. Pour the liquid mixture preheated to 170°C into the powder mixture at 180°C, continue to heat to 260°C, and stir with a high-speed mixer at 800 rpm for 45 minutes.

[0058] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0059] Comparative Example 1

[0060] This comparative example provides an asphalt pavement caulking material, comprising the following raw materials in parts by weight: 12 parts of rock asphalt, 6 parts of mineral powder, 9 parts of lime, 5 parts of petroleum resin, 25 parts of aromatic oil, and 8 parts of rubber powder.

[0061] The preparation method is the same as Example 2.

[0062] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0063] Comparative Example 2

[0064] This comparative example provides an asphalt pavement caulking material, comprising the following raw materials in parts by weight: 12 parts of rock asphalt, 60 parts of gold tailings powder, 6 parts of mineral powder, 9 parts of lime, 5 parts of petroleum resin, 25 parts of aromatic oil, and 8 parts of rubber powder.

[0065] The preparation method is the same as Example 2.

[0066] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0067] Comparative Example 3

[0068] This comparative example provides an asphalt pavement caulking material, comprising the following raw materials in parts by weight: 12 parts of rock asphalt, 35 parts of ordinary Portland cement, 6 parts of mineral powder, 9 parts of lime, 5 parts of petroleum resin, 25 parts of aromatic oil, and 8 parts of rubber powder.

[0069] The preparation method is the same as Example 2.

[0070] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0071] Comparative Example 4

[0072] This comparative example provides an asphalt pavement caulking material, comprising the following raw materials in parts by weight: 25 parts of rock asphalt, 20 parts of gold tailings powder, 6 parts of mineral powder, 9 parts of lime, 5 parts of petroleum resin, 25 parts of aromatic oil, and 8 parts of rubber powder.

[0073] The preparation method is the same as Example 2.

[0074] The test items required by the specification "Pavement Heating Sealant JT / T 740-2015" were tested, and the test results are shown in Tables 1 and 2.

[0075] Test example

[0076] The performance of the asphalt pavement sealing materials of the embodiment and the comparative example was tested according to the relevant methods in "Pavement Heating Sealant" (JT / T 740-2015). The test results are shown in Tables 1 and 2.

[0077] Table 1 Performance test results of asphalt pavement crack filling materials of embodiment and comparative example -1

[0078]

[0079] Table 2 Performance test results of asphalt pavement crack filling materials of embodiment and comparative example-2

[0080]

[0081] It can be seen from Table 1 and Table 2 that the asphalt pavement caulking materials of the embodiments are excellent in ensuring low-temperature flexibility, high-temperature stability, rapid curing, and good permeability and adhesion. Comparative Examples 1 to 4 have different degrees of inadequacy in low-temperature ductility, high-temperature performance, permeability, adhesion, etc.

[0082] Application Examples

[0083] In this application example, the high-permeability and high-viscosity asphalt pavement crack filling material prepared in Example 2 is used to repair the pavement cracks in the Jinan section of G105 National Highway. The specific construction method is as follows:

[0084] 1. Mark the starting position of the crack.

[0085] 2. Use an air gun to blow through the cracks to remove debris and loose particles in the cracks.

[0086] 3. Pour the high-permeability and high-viscosity asphalt pavement caulking material prepared in Example 2 into the cracks while it is still hot, and use special caulking equipment to compact and smooth it.

[0087] 4. After grouting, cool and solidify for more than 18 minutes.

[0088] Figure 1 and Figure 2 This is a picture of the actual application of the high-permeability and high-viscosity asphalt pavement caulking material prepared in Example 2.

[0089] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings, characterized in that: The invention comprises the following raw materials in parts by weight: 8 to 15 parts of rock asphalt, 30 to 50 parts of gold tailings powder, 5 to 15 parts of mineral powder, 5 to 15 parts of lime, 2 to 6 parts of petroleum resin, 20 to 30 parts of aromatic oil and 5 to 10 parts of rubber powder.

2. The high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings according to claim 1, characterized in that: The fineness of the gold tailings powder is 50-1500 meshes.

3. The high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings according to claim 1, characterized in that: The petroleum resin is selected from at least one of aliphatic petroleum resin, aromatic hydrocarbon petroleum resin or cycloaliphatic diene petroleum resin.

4. The high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings according to claim 1, characterized in that: The aromatic oil is selected from one or more of furfural extracted oil, phenol extracted oil and methyl pyrrolidone extracted oil.

5. The high-permeability and high-viscosity asphalt pavement crack filling material based on gold tailings according to claim 1, characterized in that: The fineness of the rubber powder is 40-100 meshes.

6. The method for preparing the high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings according to any one of claims 1 to 5, characterized in that: The steps include: Preheating and mixing the petroleum resin and the aromatic oil to form a liquid mixture; The rock asphalt, gold tailings powder, mineral powder, lime and rubber powder are heated and dry-mixed to obtain a powdery mixture; The liquid mixture is added into the powder mixture, heated and stirred to obtain the product.

7. The preparation method according to claim 6, characterized in that: The preheating temperature is 150-200°C.

8. The preparation method according to claim 6, characterized in that: The temperature of the heating dry mixing is 180-200°C.

9. The preparation method according to claim 6, characterized in that: The heating and stirring temperature is 260-280° C., the stirring speed is 600-1000 rpm, and the heating and stirring time is more than 30 minutes.

10. A method for using the high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings as claimed in any one of claims 1 to 5 or the high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings prepared by the preparation method of any one of claims 6 to 9, characterized in that: The steps include: The high-permeability and high-viscosity asphalt pavement caulking material based on gold tailings is poured into the cracks of the pavement while hot, compacted and smoothed, and cooled and solidified for more than 15 minutes.

Citation Information

Patent Citations

  • High-viscosity modified crack pouring adhesive material for bituminous pavement and preparation method

    CN107722927A

  • Temperature-control high-performance solid waste asphalt concrete

    CN113024160A